Correction: On Becoming a Global Citizen: Transformative Learning Through Global Health Experiences. Issue 1 (16th March 2021) - Litzelman, Debra K.; Gardner, Adrian; Einterz, Robert M.; Owiti, Philip; Wambui, Charity; Huskins, Jordan C.; Schmitt-Wendholt, Kathleen M.; Stone, Geren S.; Ayuo, Paul O.; Inui, Thomas S.; Cottingham, Ann H.; Umoren, Rachel A.
This article details a correction to the article: (Litzelman DK, Gardner A, Einterz RM, Owiti P, Wambui C, Huskins JC, Schmitt-Wendholt KM, Stone GS, Ayuo PO, Inui TS, Cottingham AH, Umoren RA. On Becoming a Global Citizen: Transformative Learning through Global Health Experiences. Annals of Global Health . 2017 May–August; 83(3–4): 596–604. DOI: http://doi.org/10.1016/j.aogh.2017.07.005 . PMC5726429).